2023
DOI: 10.1093/mmy/myad041
|View full text |Cite|
|
Sign up to set email alerts
|

The high diversity of Scedosporium and Lomentospora species and their prevalence in human-disturbed areas in Taiwan

Abstract: Scedosporium and Lomentospora are important opportunistic pathogens causing localized or disseminated infection in humans. Understanding their environmental distribution is critical for public hygiene and clinical management. We carried out the first environmental survey in urbanized and natural regions in Taiwan. Overall, Scedosporium and Lomentospora species were recovered in 132 out of 273 soil samples (48.4%) across Taiwan. We morphologically and molecularly identified six Scedosporium species and one Lome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Scedosporium species are ubiquitous fungi that can cause pathogenic diseases in humans and animals. In recent reports, several strains of S. dehoogii were isolated from sites with high levels of human activity, including playgrounds, public parks, industrial areas, riverbanks, or agricultural areas in different countries, such as France [ 6 ], Australia [ 15 ], Thailand [ 7 , 16 ], Chile [ 9 ], India [ 17 ], Mexico [ 18 ], Sudan [ 19 ], Taiwan [ 8 ], and Austria/The Netherlands [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scedosporium species are ubiquitous fungi that can cause pathogenic diseases in humans and animals. In recent reports, several strains of S. dehoogii were isolated from sites with high levels of human activity, including playgrounds, public parks, industrial areas, riverbanks, or agricultural areas in different countries, such as France [ 6 ], Australia [ 15 ], Thailand [ 7 , 16 ], Chile [ 9 ], India [ 17 ], Mexico [ 18 ], Sudan [ 19 ], Taiwan [ 8 ], and Austria/The Netherlands [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate knowledge of the ecological niches and potential reservoirs of these species has shown that they are more common in human-impacted and polluted environments, such as agricultural soil, public parks, polluted ponds, compost, sewage, polluted water, and effluents of wastewater treatment plants [ 5 - 8 ]. In addition, hydrocarbon-contaminated soil was reported as a habitat of these fungi[ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…multisporumm and S . rarisporum 4 . In addition, according to the latest classification, Ramirez‐Garcia et al 5 .…”
Section: Introductionmentioning
confidence: 99%